Efektivitas Program CERDIK-KODE dalam Meningkatkan Pengetahuan Siswa SMA tentang Kompetensi Koding Medis melalui Pendekatan Simulasi (Lembaga Pengembangan Kinerja Dosen, 2026)
The digital transformation of healthcare requires health professionals to understand diagnostic coding based on the International Classification of Diseases (ICD), yet such knowledge is rarely introduced at the secondary school level. This community service program aimed to improve students’ knowledge of basic diagnostic coding through the CERDIK-KODE (Smart Diagnosis and Coding) program. A participatory educational approach using learning-by-doing simulation and a one-group pretest–posttest design was implemented among 36 students at SMA Negeri 2 Penajam Paser Utara, Indonesia. The intervention included interactive lectures, educational leaflets, case-based diagnostic coding simulations, group discussions, and educational games. Knowledge was assessed using pretest and posttest questionnaires and analyzed using a paired-samples t-test. The mean score increased from 5.17 ± 1.03 before the intervention to 8.64 ± 0.87 afterward, showing a statistically significant improvement (t = −41.15; p < 0.001). Students actively participated in simulations and demonstrated improved abilities to identify simple diagnoses and assign appropriate codes. These findings indicate that interactive education and case-based simulations effectively enhance students’ knowledge and health literacy regarding diagnostic coding. The CERDIK-KODE program offers an innovative model for introducing Medical Records and Health Information Management concepts at the secondary school level.